Investigating how personality traits and career anchors relate to organisational commitment and turnover intention among uniformed personnel in the South African Navy - Groenewald, Johan A (Organisational Psychology, 2025)
Employee retention remains a critical challenge in both civilian- and military organisations. Therefore, to gain a better understanding as to which individual differences may relate to retention, this study applied person-environment fit theories to investigate how personality traits and career anchors, respectfully relate to organisational commitment, and turnover intention. More specifically, a quantitative cross-sectional design was employed, inviting uniformed personnel in the South African Navy to complete a survey. The survey comprised different sections, which included the Big Five Inventory, Career Orientations Inventory, Organisational Commitment Questionnaire, and Turnover Intention Scale. Person correlation analyses revealed that some personality traits (i.e., extraversion, agreeableness, and emotional stability) were associated with higher organisational commitment, whilst low emotional stability was associated with turnover intention. Regression analysis revealed that high openness and low emotional stability positively predicted turnover intention, but none of the traits predicted organisational commitment. Furthermore, some career anchors (i.e., autonomy, entrepreneurial creativity, and lifestyle) were associated with both lower organisational commitment and higher turnover intention. Additionally, multiple linear regression showed that autonomy and lifestyle emerged as predictors of low organisational commitment, but lifestyle demonstrated higher organisational commitment. Lastly, pure challenge predicted low turnover intention. Fundamentally, insights from this research could be used to refine selection processes and inform targeted retention strategies, best aligning individual differences with the organisation's culture, values, and needs.